Crustal Structure of Turkey from Aeromagnetic, Gravity and Deep Seismic Reflection Data - Ates, Abdullah; Bilim, Funda; Buyuksarac, Aydin; Aydemir, Attila; Bektas, Ozcan; Aslan, Yasemin (Springer, 2012)
In this paper, aeromagnetic and gravity anomalies obtained from the General Directorate of Mineral Research and Exploration were subjected to upward continuation to 3 km from the ground surface to suppress shallow effects and to expose only regional, deep sources. Then, a reduction to pole (RTP) map of aeromagnetic anomalies was produced from the 3 km upward continued data. A sinuous boundary to the south of Turkey is observed in the RTP map that may indicate the suture zone between the Anatolides and African/Arabian Plates in the closure time of the Tethys Ocean. The sinuous boundary can be correlated with the recent palaeo-tectonic maps. The southern part of the sinuous boundary is quite different and less magnetic in comparison with the northern block. In addition, maxspots maps of the aeromagnetic and gravity anomalies were produced to find out and enhance the boundaries of tectonic units. Crustal thickness, recently calculated and mapped for the western Turkey, is also extended to the whole of Turkey, and the crustal thicknesses are correlated with the previous seismological findings and deep seismic sections. The average crustal thickness calculations using the gravity data are about 28 km along the coastal regions and increase up to 42 km through the Iranian border in the east of Turkey. Density and susceptibility values used as parameters for construction of two-dimensional (2D) gravity and magnetic models were compiled in a table from different localities of Turkey. 2D models indicate that all of the anomalous masses are located in the upper crust, and this could be well correlated with the earthquakes which occurred at shallow depths.
Keywords: Upward continuation; Reduction to the pole; Maxspots; Turkey; Crustal thickness